The Effects of Human Resources Development on Financial Performance of Organisations - Odumeru, James Adetunji; Ilesanmi, Oladele Ayodeji (Asian Business Review, 2013)
Contemporary organisation invests huge resources on a regular basis on Human Resources Development (HRD) initiatives because of the age long belief that this will enhance efficiency and effectiveness. But sadly, these expectations often go unfulfilled. This study empirically tests the effect of HRD on financial performance with employee competence and organisational commitment acting as mediating mechanisms. A total of 84 copies of a questionnaire that was distributed to and received from bank workers of two of Nigeria’s leading banks: First Bank of Nigeria Plc and Zenith Bank Plc to elicit relevant data on employee participation in and perceived benefits of HRD, commitment & competence and financial performance were analysed using Cronbach’s Coefficient Alpha and multiple regression analysis. Results show a significant relationship between employee participation in HRD including perceived benefits of HRD and organisational commitment and employee competence. The study also shows a significant relationship between competence & commitment and financial performance. Thus organisation should focus attention on delivering consistent HRD initiatives relevant to the need of employees and focused on addressing identified Skills, Knowledge and Abilities (KSA) gaps for a continuous financial performance improvement. JEL Classification Code: M120